Penilaian Lima Tugas Keluarga pada Keluarga dengan Anggota Keluarga Menderita TB Paru di Wilayah Kerja BP-4 Magelang - Wahyudi,; Upoyo, Arif Setyo (Jurnal Keperawatan Soedirman, 2008)
Tuberculosis is one of the contagion diseases which is high of painfulness number and its death. The role of family is very needed to efficacy of medication of tuberculosis. The reason is that family represents the elementary system in sociaty where healthy behaviour and treatment of health is arraged. Moreover family takes charge of especial start and coordinates service given by the nurse as health professional.This research aims to investigate how family applies five familyÃ¢â‚¬â„¢s duties in the field of health. This research utilises qualitative study with the approach of fenomenology. Data collecting method was an interview and observation. Participant of this research was the family who has one of the family member suffering from tuberculosis with positif BTA and lives in Magelang.The result of ressearch shows that family recognise tuberculosis after contact with health facility. Then, the decision is taken by family to find out the medication for the member. The family provide caring for the member such as giving the nutrition, preventing the infection. The low economic status influence providing the nutrition. Workload of the family also can affect in improving health environment. Health facility especially expence is the family choice in caring for member with tuberculosis.Ã‚Â Ã‚Â Ã‚Â